The structural basis for high‐affinity uptake of lignin‐derived aromatic compounds by proteobacterial TRAP transporters. (18th August 2021) - Bisson, Claudine; Salmon, Robert C.; West, Laura; Rafferty, John B.; Hitchcock, Andrew; Thomas, Gavin H.; Kelly, David J.
Abstract : The organic polymer lignin is a component of plant cell walls, which like (hemi)‐cellulose is highly abundant in nature and relatively resistant to degradation. However, extracellular enzymes released by natural microbial consortia can cleave the β‐aryl ether linkages in lignin, releasing monoaromatic phenylpropanoids that can be further catabolised by diverse species of bacteria. Biodegradation of lignin is therefore important in global carbon cycling, and its natural abundance also makes it an attractive biotechnological feedstock for the industrial production of commodity chemicals. Whilst the pathways for degradation of lignin‐derived aromatics have been extensively characterised, much less is understood about how they are recognised and taken up from the environment. The purple phototrophic bacterium Rhodopseudomonas palustris can grow on a range of phenylpropanoid monomers and is a model organism for studying their uptake and breakdown. R . palustris encodes a tripartite ATP‐independent periplasmic (TRAP) transporter (TarPQM) linked to genes encoding phenylpropanoid‐degrading enzymes. The periplasmic solute‐binding protein component of this transporter, TarP, has previously been shown to bind aromatic substrates. Here, we determine the high‐resolution crystal structure of TarP from R. palustris as well as the structures of homologous proteins from the salt marsh bacterium Sagittula stellata and the halophile Chromohalobacter salexigens, which also grow on lignin‐derived aromatics. In combination with tryptophan fluorescence ligand‐binding assays, our ligand‐bound co‐crystal structures reveal the molecular basis for high‐affinity recognition of phenylpropanoids by these TRAP transporters, which have potential for improving uptake of these compounds for biotechnological transformations of lignin. Abstract : Lignin, the most abundant aromatic polymer on earth, is eventually degraded to monomers called hydroxycinnamates (HCMs) that can be imported by an unusual family of transporters, the Tripartite ATP‐independent Periplasmic (TRAP) transporters, which are enriched in marine proteobacteria. Here, we reveal the structural basis of HCM binding to several TRAP‐binding proteins, knowledge which will help in exploiting TRAP transporters for the production of commercially valuable chemicals from lignin‐derived feedstocks.